2022
DOI: 10.1002/adfm.202202456
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Packing and Charge Transport Behaviors of Semiconducting Polymers Over a Wide Temperature Range

Abstract: The molecular packing and resultant charge transport behaviors of semiconducting polymers are widely known to be temperature‐dependent. Due to the limitation of measurement methods, previous studies on molecular packing behavior have been mainly focused on a very limited temperature range, and therefore cannot support the understanding of charge transport behaviors. In this study, with a homemade temperature‐dependent grazing incidence XRD measurement chamber, the relationship between molecular packing structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…A similar result was also reported for another donor−acceptor-type conjugated polymer, namely DPP-4T, that the transition temperature determined from the thermal expansion of lamellar stacking is 62 °C lower than that of π−π stacking, which is ascribed to the difference in glass transition temperatures between the side chain and backbone. 33 For the P(NDI2OD-T2) batch in the present study, neither exothermic nor endothermic peaks can be identified from the DSC curve (Figure S9). Nevertheless, a good agreement is found between the π−π transition temperature and the theoretically calculated backbone glass transition temperature (274 °C) using the semiempirical correlation model developed by Xie et al (supplementary note 3 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A similar result was also reported for another donor−acceptor-type conjugated polymer, namely DPP-4T, that the transition temperature determined from the thermal expansion of lamellar stacking is 62 °C lower than that of π−π stacking, which is ascribed to the difference in glass transition temperatures between the side chain and backbone. 33 For the P(NDI2OD-T2) batch in the present study, neither exothermic nor endothermic peaks can be identified from the DSC curve (Figure S9). Nevertheless, a good agreement is found between the π−π transition temperature and the theoretically calculated backbone glass transition temperature (274 °C) using the semiempirical correlation model developed by Xie et al (supplementary note 3 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 64%
“…Regarding this discrepancy, we speculate that it is due to the different mobility of the stiff backbones and flexible side chains in P­(NDI2OD-T2), with the latter being more mobile, hence exhibiting a lower glass transition temperature. A similar result was also reported for another donor–acceptor-type conjugated polymer, namely DPP-4T, that the transition temperature determined from the thermal expansion of lamellar stacking is 62 °C lower than that of π–π stacking, which is ascribed to the difference in glass transition temperatures between the side chain and backbone . For the P­(NDI2OD-T2) batch in the present study, neither exothermic nor endothermic peaks can be identified from the DSC curve (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that NS-Octulene-3 exhibited thermally activated charge-transport features with the temperature increasing from 20 to 100 °C, , and when the operating temperature further increased, the electrical performance decreased mainly due to thermally induced molecular packing variation, , which was proved by thermogravimetric analysis and variable temperature 2D GI-XRD measurements (Figures S23 and S29). It was found that the packing distance increased obviously, and the molecular stacking structure could hardly be maintained at elevated temperatures, presumably due to the molecular thermodynamic movement (Figure S29), , as a result of which the charge carrier transport becomes more difficult and results in the decreased electrical performance. , …”
Section: Resultsmentioning
confidence: 99%
“…It was found that the packing distance increased obviously, and the molecular stacking structure could hardly be maintained at elevated temperatures, presumably due to the molecular thermodynamic movement (Figure S29), 24,26 as a result of which the charge carrier transport becomes more difficult and results in the decreased electrical performance. 24,27 ■ CONCLUSIONS…”
Section: ■ Introductionmentioning
confidence: 99%
“…After 100 °C TA of the polymers, their 2D-GIWAXS peaks became narrower and stronger. However, Zhao et al 47 recently demonstrated that, as the degree of thermal motion increases, the lattice vibrations of the crystalline domain increase, triggering π−π stacking to destroy the packed structures. After 200 °C TA, Asy-PDTS showed an amorphous morphology with the face-on domain totally collapsed.…”
mentioning
confidence: 99%